2016
DOI: 10.3389/fmicb.2016.00144
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Infections Caused by Non-toxigenic Vibrio cholerae non-O1/non-O139

Abstract: Vibrio cholerae is an aerobic, sucrose fermentative Gram-negative bacterium that generally prevails in the environment. Pathogenic V. cholerae is well-known as causative agent of acute diarrhea. Apart from enteric infections, V. cholerae may also cause other diseases. However, their role in causing extraintestinal infections is not fully known as it needs proper identification and evaluation. Four cases of extraintestinal infections due to V. cholerae non-O1/non-O139 have been investigated. The isolates were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 16 publications
3
32
0
2
Order By: Relevance
“…These risk factors indicated that immunocompromised individuals were more susceptible to NOVC. 12 The patient in our study had a degree of hepatic impairment, which was in accordance with the susceptibility factors of NOVC infection. The review showed that middleaged men were at high risk for NOVC infection.…”
Section: Risk Factorssupporting
confidence: 82%
See 1 more Smart Citation
“…These risk factors indicated that immunocompromised individuals were more susceptible to NOVC. 12 The patient in our study had a degree of hepatic impairment, which was in accordance with the susceptibility factors of NOVC infection. The review showed that middleaged men were at high risk for NOVC infection.…”
Section: Risk Factorssupporting
confidence: 82%
“…Our review included 23 cases of NOVC bacteremia described in 18 reports from 2015-2019 (Table 2). [1][2][3][4][5]7,[10][11][12][13][14][15][16][17][18][19][20][21] The male-to-female ratio was 3.6:1, and the median age was 56 years. The youngest patient developed this disease at only 3 days of age, and the oldest patient was 83 years old.…”
Section: Discussion Epidemiologymentioning
confidence: 99%
“…Several genetic elements, including R plasmids, the class I integron and the SXT element, have been reported to be closely associated with the spread of genetic elements by mediating antibiotic resistance in V. cholerae (Pan et al, 2008;Dalsgaard et al, 2000;Hochhut et al, 2000). In contrast, most non-O1/non-O139 V. cholerae strains were sensitive to the third-generation cephalosporins, fluoroquinolones, piperacillin/tazobactam, tetracyclines, chloramphenicol according to the previous studies (Chowdhury et al, 2016;Hao et al, 2015;Lu et al, 2014). A few strains were resistant to third-generation cephalosporins because of carrying gene encoding extended-spectrum-lactamase (ESBL) (Ismail et al, 2013;Petroni et al, 2002).…”
Section: Discussionmentioning
confidence: 76%
“…cholerae is the pathogen that causes cholera and is classified into more than 200 serogroups based on the somatic O surface antigen. Only the serogroups O1 and O139 V. cholerae can cause epidemic or outbreaks, whereas the non-O1/non-O139 serogroups have also been associated with cholera-like diarrhoea and systematic infections including septicemia, urinary tract infection (Chowdhury et al, 2016), peritonitis (Lan et al, 2014), skin and soft tissue infection (Maraki et al, 2016), meningitis (Hao et al, 2015), bacterial emphysema (Lai et al, 2012). Though V. cholerae non-O1/ non-O139 serogroups generally lack several major virulence factors such as cholera toxin (ctx) and toxin-coregulated pilus (tcp), a number of synergistic factors which play roles in the infection process have been identified (Singh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Para tipificar las diferentes cepas de V. cholerae se utiliza un antígeno localizado en su membrana externa denominado O, porción más externa del lipopolisacárido (LPS), correspondiendo las cepas de V. cholerae toxigénico, generalmente al tipo O1 o O139. Cepas de origen ambiental de esta bacteria presentan diversos subtipos de antígeno O denominándose en su conjunto como no-O1, no-O139 [1][2][3] . Se ha descrito que algunas cepas de V. cholerae no-O1, no-O139 poseen un claro poder patógeno con la potencialidad de causar brotes o casos esporádicos de gastroenteritis e infecciones extra-intestinales fatales en humanos [3][4][5] .…”
Section: Introductionunclassified